Environmental Homeopathy: Homeopathic Potencies Regulate the Toxicity and Growth of Raphidiopsis raciborskii (Cyanobacteria) and can be Tracked Physico-Chemically. Part 1: Biological Results - Mohammad, Suham Nowrooz; Pinto, Andreia Adelaide G.; Silva, Rodrigo Augusto da; Suffredini, Ivana Barbosa; Tournier, Alexander L.; Cartwright, Steven J.; Yunes, João Sarkis; Bonamin, Leoni V. (Homeopathy, 2024)
Introduction Cyanobacteria are microorganisms found in many parts of the world and several genera, such as Raphidiopsis raciborskii, are producers of cyanotoxins. Homeopathic potencies have been found to modulate toxicity in different biological models, and the present study endeavors to discover whether this might also be the case with cyanobacteria.Objectives Our objective was to investigate the possible effects of homeopathic potencies on the resilience of Artemia franciscana (brine shrimp) embryos to saxitoxin (STX; cyanotoxin) and on controlling the growth of R. raciborskii in vitro.Method A. franciscana cysts were cultivated in seawater in 96-well plates to evaluate the hatching rate and vitality, plus the gene expression of heat shock proteins (HSPs), after being challenged with R. raciborskii extract containing 2.5 µg/L of STX and treated with different homeopathic potencies. Untreated wells were used as controls (“base-line”). Potencies were chosen from a screening process based on seven selected homeopathic preparations according to the similitude of STX symptoms (Sulphur, Zincum metallicum, Nitric acidum, Plumbum metallicum, Mercurius solubilis, Phosphoric acidum, Isotherapic from R. raciborskii extract; all at 6cH, 30cH and 200cH). Cultures of R. raciborskii maintained in an artificial seawater medium were equally treated with screened homeopathic potencies selected from the same list but specifically for their growth control as a function of time.Results A 15% lower rate of hatching of A. franciscana cysts was observed after treatment with Nitric acidum 6cH in comparison with baseline (p = 0.05). A complete toxicity reversal was seen after treatment with Isotherapic 200cH, with a 23-fold increase of Hsp 26 gene expression (p = 0.023) and a 24-fold increase of p26 gene expression (p ≤ 0.001) in relation to baseline. Nitric acidum 200cH and Mercurius solubilis 30cH limited the exponential growth of cyanobacteria up to 95% and 85% respectively (p ≤ 0.003) in relation to baseline. Succussed water presented only a transitory 50% inhibition effect.Conclusion Isotherapic 200cH improved A. franciscana bioresilience to STX; Nitric acidum 200cH and Mercurius solubilis 30cH showed the optimal performance on limiting R. raciborskii growth. The results point to the potential of homeopathic potencies to mitigate environmental problems related to water quality.
Keywords: saxitoxins; Artemia franciscana; bioresilience; water; HSPs; eco-toxicology